Is the Womb Barren? A Located Study of Spiritual Tourism in Sedona, Arizona, and Its Possible Effects on Eco-consciousness - Coats, Curtis D. (Journal for the study of religion, nature and culture, 2008)
Ancient people considered Sedona, Arizona, the womb of Earth. This is only part of the story of Sedona that has made it a spiritual tourist destination. Some estimate that well over one million New Age pilgrim-tourists travel there annually to experience the vortices, or energy spots, in the Earth’s womb. These visitors will find different spiritual practitioners in Sedona, but they will find at least one common thread. The red rocks of Sedona hold great mystical power - a power that is explained with an eclectic mix of New Age metaphysics and modern science. Using field data from in-depth interviews, text analysis and participant observation, I will detail the content and contours of the scientific-spiritual worldview embedded in Sedona’s landscape and embodied by its pilgrim-tourists. Also, I will address possibilities for eco-consciousness embodied in the lived experience of this worldview.